Diseño Conceptual de un Sistema de Generación de Energía Eléctrica Sustentable a partir de Metano generado por Digestión Anaerobia: Integración con Procesos Electroquímicos para Tratamiento de Contaminantes en Agua y Análisis Económico - Barreneche Vásquez, Johan Sebastián (Universidad Antonio Nariño, 2024)
This study investigated the feasibility of using a biogas electricity generation system to mitigate the high energy costs associated with electrochemical advanced oxidation processes (EAOPs) in the removal of persistent contaminants in water. The energy consumption of the Electro-Fenton (EF) system in the degradation of the Losartan compound and the inactivation of microorganisms was evaluated in two environments: controlled conditions and irrigation water.